Evaluasi Efektifitas Dinas Perhubungan Sukabumi dalam penyediaan PJU di Kadudampit sesuai Permenhub No. 47 Tahun 2023 - Muhamad Fajri Nur Rizki; Temmy Fitriah (Amandemen: Jurnal Ilmu pertahanan, Politik dan Hukum Indonesia, 2026)
Public street lighting (PJU) is an important infrastructure in supporting the safety and comfort of road users. The provision of PJU is the responsibility of the Sukabumi Regency Transportation Agency, which must be carried out in accordance with Minister of Transportation Regulation No. 47 of 2023 concerning Street Lighting Equipment. This study aims to determine the effectiveness of the Sukabumi Regency Transportation Agency in providing PJU in the Kadudampit District. The research method used was qualitative with a descriptive approach. Data collection was carried out through field observations, interviews, and documentation studies. The results of the study indicate that the provision of PJU in Kadudampit Subdistrict is not yet fully effective, as indicated by the existence of PJU that is not functioning optimally and uneven distribution. The main obstacles faced include budget and maintenance limitations. Nevertheless, the implementation of street lighting provision has been in accordance with the provisions of Permenhub No. 47 of 2023. Therefore, improved planning and supervision are needed to increase the effectiveness of street lighting provision.